Servicio de capacitación y preparación de expositores en la ciudad de Babahoyo - Jaime Camacho, Leslie Ariana (2020)
Currently there is complementary work in the educational and professional field whereby educational institutions due to various factors, such as time or planning, prevent the comprehensive training of children, young people and professionals who develop their own attitudes to express themselves appropriately. in front of an auditorium with a large volume of attendees, as well as the personalization of academic works that promote self-education and the acquisition of real knowledge around their life experience. These causes allow the development of the entrepreneurship proposal of an advisory and training center for "Ideary" exhibitors in the city of Babahoyo, due to the fact that the businesses that offer this type of services are minimal, which generates an advantage for attracting and Customer loyalty, this will be available to the public, with highly qualified professionals who will be in charge of forming individuals with clear ideas regarding the current situation as well as being and appearing as an exhibitor that transmits knowledge during their intervention